WITHDRAWN - Sporadic Variant of Cone-Rod Dystrophy-20 - Mahato, Ghana Shyam; Shrestha, Anju (Journal of Bharatpur Hospital, 2025)
On 20th November 2025 this article was withdrawn on the request of the primary author.